Isolation and Identification of Molds Companid of Rice Seeds In ALDiwania City and Study of Effect different temperature on Growth of fungus Curvularia tuberculata . - Ebtesam Thamer Jeaz; Majed Kadem Aboud (Al-Qadisiyah Journal of Pure Science, 2018)
Collected (5) samples of  rice seeds from saylow AL diwania  city ( 1 kilow ) named (yasamin 2010)Results  of isolation and identification of fungus from rice samples were as follow: Aspergillus genera in treatment by rice grains by hypochlorite of sodium 34 % while in non treatment rice grains 35 % and isolated curvularia germ in treatment rice grains 0.3 % while untreatment 1.3 % Presented by C.tuberculata and isolated many of different genera and different isolationpercentage. On the other hand, the highest percentage ofC urvularia tuberculata          growth was recorded in July and November with 28.5 % while lower percentage was in May with 0%.The results also showed the range of growth was much higher in temperatures ( 25 â€“ 40) CÙ’ by range ( 6.4 , 6.5 , 6.8 , 6.4 ) cm while in ( 50, 55 ) cÙ’ it was found myceliumonly, in ( 60 â€“ 75 ) CÙ’  founded conidia only but in ( 80 â€“ 100 ) CÙ’ not found mycelium or conidia in culture.